GAMBARAN PENGGUNAAN ANTIBIOTIK ORAL TANPA RESEP DOKTER PADA MASYARAKAT RW 010 KELURAHAN JATINEGARA KECAMATAN CAKUNG JAKARTA TIMUR PERIODE MARET – MEI 2019 - Dessy Adelia; Vonny Nofrika; Atika Esti Thama (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2021)
Used antibiotics should take into account the patient's previous medical history. Consumption of antibiotics patients should be also considered, such as the type, dose and duration of use antibiotics. The badly supervision of antibiotic sales without a doctor's prescription makes people free to buy antibiotics anytime and anywhere. The purpose of the study was to determine the overview using oral antibiotics without prescription in RW 010 Kelurahan Jatinegara Kecamatan Cakung East Jakarta Period March – May 2019. The method used is descriptive method. From the results of the study obtained an overview using oral antibiotics without prescription is still widely used by the community, based on the way people get oral antibiotic drugs is by buying selfish at a pharmacy without a doctor’s prescription as many as 121 respondents (45.83%) and people who bought oral antibiotics at the drugstore were 108 respondents (40.91%), and others people get antibiotics by buying with prescription as many as 35 respondents (13.26%). Class of oral antibiotic its many used of people without a doctor’s prescription are penicillins that as many as 176 respondents (66.67%), and to used the most rarely macrolides as many as 23 respondents (8.71%). The reason people used drugs without a doctor’s prescription oral antibiotic that is because previously prescribed by the doctor as many as 97 respondents (36.74%), and the suggested by a friend or relative as many as 21 respondents (7.96% ). Complaining of pain is often experienced by people on the used of oral antibiotics drugs without a doctor’s prescription that is as pain relief or pain as much as 96 respondents (36.36%), and to used the most rarely experienced that as an acne medicine as many as 23 respondents (8.71%).